Financial Performance Evaluation of Fast-Food Restaurant - Munazza Zahra; Meenu Baliyan; Jasmine Tan; Hooi Jin Tan; Xin Way Tan; Siti Nazatul Huda Binti Nordin; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
This study examines McDonald's financial performance from 2019 to 2023, focusing on key financial metrics such as profitability, operational efficiency, liquidity, solvency, and cash flow. The objective is to assess McDonald's financial health and identify factors contributing to its sustained market leadership in the fast-food industry. Using descriptive statistics and regression analysis, the study evaluates McDonald's financial ratios, including operating profit margin, return on assets, inventory turnover, and current ratio, among others. The results reveal strong profitability and effective cost control, with a consistent operating profit margin and robust asset management. McDonald's liquidity is sufficient to meet short-term obligations, and its prudent debt management reflects financial stability. The company’s investment in digital transformation and operational improvements, such as streamlined inventory management and enhanced customer engagement, have further contributed to its financial resilience. In conclusion, McDonald's has demonstrated adaptability and resilience amidst external challenges, ensuring continued financial success. The study suggests that McDonald's should continue investing in digital platforms and menu innovation to meet evolving customer preferences. The implications of these findings are significant for the fast-food industry, highlighting the importance of strategic financial management in maintaining market leadership and long-term growth.